Rupturing "AI for Good": A Feminist Decolonial Theoretical Framework for Analyzing AI Interventions in Gender-Based Violence - Mesa Velez, Lucia Fernanda (AoIR Selected Papers of Internet Research, 2026)
This paper develops a critical theoretical framework for analyzing "AI for Good" interventions addressing gender-based violence (GBV) from feminist and decolonial perspectives. While empirical studies demonstrate artificial intelligence (AI)'s potential benefits for GBV interventions, critical scholarship reveals how these technologies often reproduce harmful power structures. The proposed framework bridges this divide through four interconnected analytical dimensions: epistemological foundations (examining whose knowledge shapes interventions), material infrastructure (revealing extractive processes enabling AI systems), power distribution (analyzing decision-making structures), and transformative potential (the role of the intervention in perpetuating or challenging systems of oppression).Based on a critical discourse analysis of, “AI for Good” literature, AI ethics and governance frameworks, and meta-analyses of GBV interventions’ empirical studies, and a literature review of feminist science and technology studies and decolonial approaches to technology, the framework operationalizes feminist analyses that expose design choices that embed gender-based assumptions and limit accessibility (Klein & D’Ignazio, 2024; Costanza-Chock, 2020; Criado-Perez, 2019) and decolonial perspectives that reveal how infrastructures interact with institutional systems to perpetuate colonial structures (Couldry & Mejias, 2018; Ricaurte, 2019; Mohamed et al., 2020; Madianou, 2025). This framework challenges "AI for good" narratives that function as moral shields obscuring exploitative data extraction and power asymmetries (Madianou, 2025). By translating abstract theoretical concepts into concrete analytical tools, the framework enables researchers to systematically examine power dynamics in AI interventions, center survivor knowledge, and imagine alternative approaches that challenge rather than reinforce existing hierarchies in addressing gender-based violence.